A Randomized, Placebo‐Controlled, Double‐Blind Study of the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of Single and Repeated Doses of Mirogabalin in Healthy Asian Volunteers. Issue 6 (17th April 2018) - Jansen, Mendel; Warrington, Steven; Dishy, Victor; Ohwada, Shoichi; Johnson, Lisa; Brown, Karen; Ishizuka, Hitoshi
Abstract: Mirogabalin is a novel, preferentially selective α2 δ‐1 ligand under investigation to treat neuropathic pain. The purpose of this study was to evaluate the safety, tolerability, and pharmacokinetics of various doses of mirogabalin in healthy subjects of different ethnicities. This randomized, placebo‐controlled, double‐blind, sequential, ascending‐dose study evaluated single (10‐40 mg) and repeated (10, 15 mg twice a day) doses of mirogabalin in Japanese subjects, and a single dose of mirogabalin in Korean, Chinese, and white subjects. Mirogabalin was rapidly absorbed, with a median time to maximum plasma concentration of 1 hour, and rapidly eliminated, with a mean elimination half‐life of 2 to 3 hours. Single‐dose mirogabalin pharmacokinetic parameters were comparable between Asian and white subjects. Exposure increased proportionally as mirogabalin dose increased in Japanese subjects. Mean mirogabalin steady‐state clearance and volume of distribution values were comparable across dose levels. No accumulation of mirogabalin was observed on repeated dosing in Japanese subjects. Mirogabalin had an acceptable safety and tolerability profile in Asian and white subjects at doses up to 15 mg twice a day for 7 days. The most common treatment‐emergent adverse events (somnolence, headache, and dizziness) were consistent with the known mechanism of action and safety profile of mirogabalin.